Global Psychological Implications of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Coronavirus Disease-2019 (COVID-19). What Can Be Learned From Italy. Reflections, Perspectives, Opportunities - De Giorgio, Andrea (Frontiers in Psychology, 2020)
On 31 December 2019, the Chinese authorities announced that in the city of Wuhan, Hubei Province, central-eastern China, a cluster of pneumonia cases of unknown aetiology had developed. A new coronavirus (SARS-CoV-2) that causes serious problems like pneumonia and even death, has been discovered. This new disease (COVID-19) has spread also in Italy starting from the first recognized case on 20th of February. Beyond its biological implications, this coronavirus allows us many psychological reflections. A new virus is indeed a potentially serious problem for mankind, but it can also be an opportunity to bring the focus back to us, to observe what is happening, who we are and how we are reacting both as individuals and as a population. Even positive implication of this pandemic was discussed.